A metal paste and its packaging base

CN117594283BActive Publication Date: 2026-10-09CHAOZHOU THREE CIRCLE GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311681072.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-08
Publication Date
2026-10-09
Estimated Expiration
2043-12-08

AI Technical Summary

Technical Problem

但常规使用金属浆料印刷形成金属层浆料后需要与陶瓷层共烧,传统金属浆料的导电相一般为Ag、Au、Pd、Pt等贵金属,此类金属熔点较低,烧成温度约为800℃~1000℃,与陶瓷件在高温共烧下极易被氧化,氧化后形成黑色氧化层表面,导致影响其在应用端的定位功能

Benefits of technology

[0038] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a metal paste and its encapsulation base. By improving the formulation of the metal paste, a metal paste with good oxidation resistance is prepared and used in the preparation of the metal layer in PKG to obtain a ceramic encapsulation base with good bonding performance between the metal layer and the ceramic substrate, good oxidation resistance of the metal layer, accurate positioning, long service life and excellent electrical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004596184330000051
    Figure BDA0004596184330000051
  • Figure BDA0004596184330000061
    Figure BDA0004596184330000061
  • Figure BDA0004596184330000062
    Figure BDA0004596184330000062
Patent Text Reader

Abstract

The application belongs to the field of electronic packaging materials, and particularly discloses a metal paste and a packaging base thereof.The metal paste comprises the following components in mass percentage: 75-90% of conductive powder, 3-7% of alumina, 0.5-2% of organic resin, 0.5-3% of niobium-containing compound, and the balance of organic solvent.The metal paste has good oxidation resistance, and can obtain a ceramic packaging base with good bonding performance between the metal layer and the ceramic substrate, good oxidation resistance of the metal layer, accurate positioning, long service life and excellent electrical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electronic packaging materials, specifically relating to a metal paste and its packaging substrate. Background Technology

[0002] With the rapid development of electronic information technology, electronic products are becoming increasingly smaller, more portable, and more multifunctional, which in turn raises the requirements for electronic packaging materials and related packaging technologies.

[0003] In the field of electronic packaging, ceramic packaged boxes (PKGs) are most commonly used to encapsulate various electronic devices. A packaged box is fabricated by forming a metal layer with a specific structure on a ceramic layer, giving it good conductivity and positioning capabilities to facilitate the connection between the chip and the circuit board. However, conventional metal paste printing requires co-firing with the ceramic layer. The conductive phase of traditional metal pastes is typically precious metals such as Ag, Au, Pd, and Pt. These metals have low melting points and are fired at temperatures of approximately 800℃ to 1000℃. Under high-temperature co-firing with ceramic components, they are easily oxidized, forming a black oxide layer that affects their positioning function in applications. Furthermore, to prevent oxidation of the metal layer during high-temperature co-firing or subsequent use due to prolonged contact with air, existing technologies use corrosion-resistant metal electroplating to protect the metal layer. However, for PKG products with different designs, some areas are not fully conductive with the overall product, resulting in incomplete electroplating and failing to provide adequate insulation against oxidation. Therefore, the problem of the metal layer being easily oxidized persists. Summary of the Invention

[0004] In view of the problem of easy oxidation of the metal layer in the ceramic packaging substrate involved in the above-mentioned prior art, the present invention will provide a metal paste and its packaging substrate.

[0005] To achieve the above objectives, the following technical solutions are specifically provided:

[0006] A metal paste comprising the following components in weight percentage: 75-90% conductive powder, 3-7% alumina, 0.5-2% organic resin, 0.5-3% niobium-containing compound, and the balance being organic solvent.

[0007] In the technical solution of this invention, the oxidation resistance of the metal slurry during sintering is improved by the synergistic effect of alumina, conductive powder, and niobium-containing compounds. Specifically, during the co-firing process of the metal slurry and ceramics, the glass phase in the ceramic substrate tends to migrate to the metal layer due to capillary action. The oxide (Al2O3) in the metal layer has good wettability with the glass phase. The migration amount of the glass phase can be controlled by adjusting the alumina (Al2O3) content in the metal slurry, thereby directionally precipitating a glass phase protective layer on the surface of the metal layer and improving the oxidation resistance. If the alumina powder content is too low, it will reduce the migration amount of the glass phase during sintering, affecting the formation of the protective layer on the slurry surface and reducing the oxidation resistance. If the alumina content is too high, the glass phase migration is excessive, making it easy to sublimate and lose during sintering, thus failing to achieve the oxidation resistance effect on the slurry surface.

[0008] Preferably, the molar ratio of the conductive powder to the niobium-containing compound is (36-260):1.

[0009] More preferably, the molar ratio of the conductive powder to the niobium-containing compound is (60-115):1.

[0010] Preferably, the mass ratio of the conductive powder to the alumina is (14-20):1.

[0011] Preferably, the ratio of the average particle size of the alumina to the conductive powder is (1-6):1.

[0012] More preferably, the ratio of the average particle size of the alumina to the conductive powder is (2-5):1.

[0013] Meanwhile, the inventors discovered that the content and particle size of alumina and conductive powder need to be matched. When the mass ratio of alumina to conductive powder is too small, or the ratio of the average particle size of alumina to conductive powder is too small, agglomeration is very likely to occur during the dispersion process of preparing the slurry. After sintering, the alumina is unevenly distributed, which in turn leads to uneven distribution of the glass phase and weakens the oxidation resistance of the slurry. When the mass ratio of alumina to conductive powder is too large, or the ratio of the average particle size of alumina to conductive powder is too large, the dispersibility is poor during the mixing process with conductive powder due to the large difference in content or particle size. Uneven distribution of alumina leads to uneven distribution of the glass phase, thereby weakening the oxidation resistance. Furthermore, during sintering, the Nb in the niobium-containing compound forms a solid solution with the metal in the conductive powder, further enhancing the wettability of the glass phase to the elemental metal. This plays a role in the directional control of glass phase precipitation and strengthens the protective layer structure to prevent metal layer oxidation. The inventors also discovered that if the molar ratio of conductive powder to niobium-containing compound is too small, the niobium-containing compound lowers the sintering temperature of the conductive powder, leading to premature sintering and densification, which makes glass phase migration difficult, reduces the adhesion of the metal layer to the ceramic plate, and easily causes problems such as metal layer detachment. If the molar ratio of conductive powder to niobium-containing compound is too large, it cannot play a role in the directional control of glass phase precipitation, and the oxidation resistance of the metal slurry is poor.

[0014] Preferably, the niobium-containing compound includes at least one of niobium oxide (Nb₂O₅), NbO₂, and niobium chloride (NbCl₅).

[0015] Preferably, the niobium-containing compound has an average particle size of 0.7-1.8 μm.

[0016] Preferably, the niobium-containing compound has a mass percentage content of 1-2%.

[0017] Preferably, the conductive powder has an average particle size of 1-2 μm; the conductive powder includes at least one of tungsten powder, molybdenum powder, and manganese powder.

[0018] Preferably, the alumina has an average particle size of 1-6 μm.

[0019] Preferably, the conductive powder has a mass percentage content of 80-85%.

[0020] Preferably, the alumina content is 4-6% by mass.

[0021] The conductive powder is selected from at least one of tungsten powder, molybdenum powder, and manganese powder. These metal elements have high melting points, such as tungsten with a melting point of 3410℃, which can meet the requirement of not being oxidized at the co-firing temperature. At the same time, they also have good electrical and thermal conductivity.

[0022] Preferably, the organic solvent includes at least one of DOP (dioctyl phthalate), DBP (dibutyl phthalate), DEP (diethyl phthalate), and BCA (diethylene glycol monobutyl ether acetate); the organic resin includes at least one of ethyl cellulose, nitrocellulose, acrylic resin, and epoxy resin.

[0023] A method for preparing a metal slurry includes the following steps: ball milling and dispersing the components other than the organic solvent, adding the organic solvent after ball milling and stirring evenly to obtain the metal slurry.

[0024] Preferably, the ball milling time is 10-24 hours.

[0025] The present invention provides a method for preparing an encapsulation base, comprising the following steps: coating the metal paste onto a ceramic green body, followed by debinding and sintering; to obtain the encapsulation base.

[0026] Preferably, the slurry of the ceramic green body comprises the following components by mass percentage: 35-45% alumina, 3-5% SiO2, 2-4% MgO, 45-53% solvent, 2-4% binder, 0.5-1.5% dispersant, and 0.5-1.5% plasticizer, and the ceramic green body is prepared using conventional printing, spraying, or other methods in the art.

[0027] The present invention also provides a packaging base, comprising a ceramic layer and a metal layer structure.

[0028] Preferably, the metal layer structure contains W, Nb, Al, and Si.

[0029] Preferably, the metal paste is coated with at least one of printing and spraying methods.

[0030] Preferably, the mass percentage of W in the surface of the metal layer structure is 85-95%;

[0031] The mass percentage of Nb in the surface of the metal layer structure is 1-4%;

[0032] Preferably, the mass percentage of Al in the surface of the metal layer structure is 2-6%;

[0033] Preferably, the mass percentage of Si in the surface of the metal layer structure is 2-5%.

[0034] Preferably, W exists in the form of elemental W and W-Nb solid solution, with the mass ratio of elemental W to W-Nb solid solution being (20-50):1.

[0035] Preferably, Al exists in the form of Al2O3, Nb exists in the form of W-Nb solid solution, and Si exists in the form of SiO2.

[0036] After co-sintering, the surface elements of the metal layer structure are mainly W, Nb, Al, Si, and O. Si originates from the migration of the glass phase from the ceramic substrate and mainly exists in the form of elemental W, W-Nb solid solution, Al2O3, and SiO2. When the Al2O3 content is too low, it will reduce the SiO2 content during sintering, affecting the formation of a protective layer on the slurry surface and reducing oxidation resistance. When the Al2O3 content is too high, the amount of SiO2 migration is excessive, making it easy to sublimate and be lost during sintering, thus failing to achieve the anti-oxidation effect on the slurry surface. When the W-Nb solid solution content is below the specified range, the slurry has poor wetting of SiO2, weakening the anti-oxidation performance.

[0037] Preferably, the temperature for debinding is 300-500℃, the debinding time is 2-4 hours, the sintering temperature is 1400-1600℃, and the sintering time is 2-4 hours.

[0038] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a metal paste and its encapsulation base. By improving the formulation of the metal paste, a metal paste with good oxidation resistance is prepared and used in the preparation of the metal layer in PKG to obtain a ceramic encapsulation base with good bonding performance between the metal layer and the ceramic substrate, good oxidation resistance of the metal layer, accurate positioning, long service life and excellent electrical performance. Detailed Implementation

[0039] To better illustrate the purpose, technical solution, and advantages of this invention, specific embodiments will be used to further explain the invention below. Unless otherwise specified, the test methods used in the embodiments and / or comparative examples are conventional methods; the materials and reagents used, unless otherwise specified, are commercially available.

[0040] Examples 1-15 and Comparative Examples 1-6

[0041] The specific preparation process of Example 1 is as follows:

[0042] All components are based on 100 wt% metal slurry. 80.3 wt% conductive powder (W powder, average particle size 1.5 μm), 0.83 wt% Nb2O5 powder (Nb compound, average particle size 1.5 μm), and 4 wt% alumina powder (average particle size 3 μm) were weighed out and added to a ball mill for thorough ball milling and dispersion for 20 hours. After complete ball milling, 1 wt% organic resin nitrocellulose was added, with the remainder being organic solvent DOP. Stirring continued until the resin was completely dissolved to obtain a homogeneous antioxidant slurry for later use.

[0043] A ceramic green sheet slurry with the following components is prepared: 40 wt% alumina, 4 wt% SiO2, 3 wt% MgO, 48.5 wt% toluene solvent, 2.5 wt% polyvinyl butyral (PVB) binder, 1 wt% stearic acid dispersant, and 1 wt% castor oil plasticizer. The above green sheet slurry is printed to obtain a ceramic green sheet (0.24 mm). According to the required design structure, an antioxidant slurry is used to screen print a metal slurry layer (printing thickness of 25 μm) on the surface of the ceramic green sheet. After printing, the sintering is carried out at a sintering temperature of 400℃ and a sintering time of 3 hours. The sintering temperature is 1500℃ and the sintering time is 3 hours. After sintering, an encapsulation base with a metal layer and ceramic layer structure with specific components and contents is obtained.

[0044] The only difference between Examples 2-11, Comparative Examples 1-6 and Example 1 is that the components and / or contents of the conductive powder, Nb-containing compound powder, and alumina powder are different, as detailed in Table 1.

[0045] The only difference between Examples 12-14 and Example 5 is that the ratio of the average particle size of alumina powder to conductive powder is different, as detailed in Table 1. Specifically, the average particle sizes of alumina powder and conductive powder in Examples 12-14 are: alumina with an average particle size of 5 μm and conductive powder with an average particle size of 1 μm, alumina with an average particle size of 1.5 μm and conductive powder with an average particle size of 1.5 μm, and alumina with an average particle size of 6 μm and conductive powder with an average particle size of 1 μm.

[0046] The only difference between Example 15 and Example 5 is that in Example 1, 2 wt% of organic resin ethyl cellulose was added after ball milling, with the remainder being organic solvent DBP.

[0047] Table 1

[0048]

[0049]

[0050] The metal layers prepared in each embodiment and comparative example were subjected to the following performance tests, as shown in Table 2, and the test results are shown in Tables 3 and 4.

[0051] Table 2

[0052]

[0053] Table 3

[0054]

[0055]

[0056] Table 4

[0057]

[0058]

[0059] As can be seen from the above embodiments, the oxide layer thickness of the metal layer of the present invention is less than 150 nm and 70 nm under normal temperature and low humidity environments, respectively, and the bonding force between the metal layer and the ceramic substrate reaches more than 9 N. Therefore, the present invention achieves good bonding performance between the metal layer and the ceramic substrate, and a low metal oxide layer thickness, thus meeting the requirements of accurate positioning, long service life, and excellent electrical performance of the ceramic packaging substrate.

[0060] As can be seen from Examples 1-15 and Comparative Examples 1-6, the present invention improves the oxidation resistance and bonding strength of metal slurry during sintering by combining specific amounts of alumina, conductive powder and niobium-containing compounds. Preferably, the mass percentage of conductive powder is 80-85% and the mass percentage of alumina is 4-6%.

[0061] As can be seen from Examples 2-6, further controlling the ratio of conductive powder to niobium-containing compound content makes the metal slurry have better oxidation resistance and bonding strength. In this invention, the molar ratio of conductive powder to niobium-containing compound can be selected as (36-260):1, and preferably the molar ratio of conductive powder to niobium-containing compound is (60-115):1.

[0062] As can be seen from Examples 5-8, selecting W powder as the conductive powder and Nb2O5 as the niobium-containing compound results in better oxidation resistance and bonding strength of the metal paste.

[0063] As can be seen from Examples 4 and 11, further controlling the mass (content) ratio of alumina and conductive powder results in better oxidation resistance and bonding strength of the ceramic slurry. More preferably, the mass (content) ratio of alumina and conductive powder is (14-20):1.

[0064] As can be seen from Examples 11-14, further controlling the ratio of the average particle size of alumina and conductive powder results in better oxidation resistance and bonding strength of the ceramic slurry. The ratio of the average particle size of alumina and conductive powder can be selected as (1-6):1, and more preferably (2-5):1.

[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A metal paste, characterized in that, It includes the following components by mass percentage: 75-90% conductive powder, 3-7% alumina, 0.5-2% organic resin, 0.5-3% niobium-containing compound, and the balance being organic solvent.

2. The metal paste as described in claim 1, characterized in that, The molar ratio of the conductive powder to the niobium-containing compound is (36-260):

1.

3. The metal paste as described in claim 2, characterized in that, The molar ratio of the conductive powder to the niobium-containing compound is (60-115):

1.

4. The metal paste as described in claim 1, characterized in that, The mass ratio of the conductive powder to the alumina is (14-20):

1.

5. The metal paste as described in claim 1, characterized in that, The average particle size ratio of the alumina and the conductive powder is (1-6):

1.

6. The metal paste as described in claim 5, characterized in that, The average particle size ratio of the alumina and the conductive powder is (2-5):

1.

7. The metal paste as described in claim 1, characterized in that, The niobium-containing compound includes at least one of Nb₂O₅, NbO₂, and NbCl₅; the average particle size of the niobium-containing compound is 0.7-1.8 μm.

8. The metal paste as described in claim 1, characterized in that, Includes at least one of the following: The average particle size of the conductive powder is 1-2 μm; The conductive powder includes at least one of tungsten powder, molybdenum powder, and manganese powder; The alumina has an average particle size of 1-6 μm; The organic solvent includes at least one of dioctyl phthalate, dibutyl phthalate, diethyl phthalate, and diethylene glycol monobutyl ether acetate; The organic resin includes at least one of ethyl cellulose, nitrocellulose, acrylic resin, and epoxy resin.

9. A method for preparing a packaging substrate, characterized in that, The process includes the following steps: coating the metal paste according to any one of claims 1-8 onto a ceramic green body, followed by debinding and sintering; to obtain the encapsulation base.

10. A packaging substrate prepared by the method of claim 9, characterized in that, It includes a structure with ceramic and metal layers.

11. The packaging base as described in claim 10, characterized in that, The metal layer structure contains W, Nb, Al, and Si; In the metal layer structure, the mass percentage of W is 85-95%; the mass percentage of Nb is 1-4%; the mass percentage of Al is 2-6%; and the mass percentage of Si is 2-5%.

12. The packaging base as described in claim 11, characterized in that, The form of W includes elemental W and W-Nb solid solution, with the mass ratio of elemental W to W-Nb solid solution being (20~50):1.

Citation Information

Patent Citations

  • Application of additive, electrode slurry, additive slurry, positive electrode or negative electrode of lithium ion battery, preparation method of positive electrode or negative electrode of lithium ion battery, and lithium ion battery

    CN106450337A

  • Low-cost chip resistor paste

    CN113782249A